1989
DOI: 10.2134/agronj1989.00021962008100060020x
|View full text |Cite
|
Sign up to set email alerts
|

Row Spacing and Plant Population Effects on Yield Components of Soybean

Abstract: Information is needed to characterize soybean [Glycine max (L.) Merr.] plant responses where cultural practices and environmental conditions are maintained at a level conducive to high yield. Field studies were conducted in 1985 and 1986 to determine the effect of row spacing and plant population on seed yield and yield components of soybean. Two determinate Maturity Group V cultivars, Essex and Deltapine 105, were grown at three row spacings of 25, 51, and 76 cm and three plant populations of 260 200, 390 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
0
4

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 12 publications
11
49
0
4
Order By: Relevance
“…Th e two lower seeding rates had negligible plant mortality, whereas the two higher seeding rates had about 7% plant mortality. Other studies have reported a greater impact of row spacing (Ethredge et al, 1989;Oplinger and Philbrook, 1992;De Bruin and Pedersen, 2008b) or seeding rates (Ethredge et al, 1989;Board 2000) on plant mortality.…”
Section: Resultsmentioning
confidence: 91%
“…Th e two lower seeding rates had negligible plant mortality, whereas the two higher seeding rates had about 7% plant mortality. Other studies have reported a greater impact of row spacing (Ethredge et al, 1989;Oplinger and Philbrook, 1992;De Bruin and Pedersen, 2008b) or seeding rates (Ethredge et al, 1989;Board 2000) on plant mortality.…”
Section: Resultsmentioning
confidence: 91%
“…ETHREDGE et al (1989) obtiveram redução linear no rendimento de grãos do caule e dos ramos das plantas de soja com o aumento da população de plantas. Essa diminuição pode não acarretar diminuição no rendimento por área, pois o maior número de plantas compensaria o menor rendimento por planta, o que não foi observado neste trabalho.…”
Section: Resultsunclassified
“…A redução do espaçamento entre linhas tem se constituído numa prática vantajosa, em que, na maioria dos experimentos, houve incremento do rendimento. Diversos trabalhos, utilizando espaçamentos entre linha de 17cm até 100cm, têm verificado acréscimos de até 40% no rendimento (HERBERT & LITCHFIELD, 1982;ETHREDGE et al 1989;BOARD et al, 1990;PIRES et al, 1998;VENTIMIGLIA et al, 1999) com a redução do espaçamento. Este aumento no rendimento tem sido associado a vários fatores, como o melhor uso da água devido ao sombreamento mais rápido do solo, melhor distribuição de raízes, redução da competição intraespecífica, maior habilidade de competição com plantas daninhas, exploração uniforme da fertilidade do solo e maior e mais rápida intercepcão da energia solar.…”
Section: Introductionunclassified
“…Le nombre de gousses par plant était maximal et variait de 25 à 32 gousses plant -1 pour des densités de peuplement de 30 plants m -2 et atteignait un minimum de 15 gousses plant -1 à des densités de 70 à 80 plants m -2 . Weber et al (1966), Hicks et al (1969), Goli et Olsen (1983) et Ethredge et al (1989 avaient obtenu des résultats similaires dans leurs études. Le nombre de gousses plant -1 du cultivar 9063 était générale-ment supérieur aux nombres de gousses plant -1 des deux autres cultivars.…”
Section: Résultats Et Discussionunclassified